UNPACKING THE ECONOMIC SIGNIFICANCE OF MICE: EVIDENCE FROM DOMESTIC MICE TOURISM IN INDONESIA - Addin Maulana; Ramadhan Pancasilawan; Entang Adhy Muhtar; Slamet Usman Ismanto (Politeknik Pariwisata Makassar, 2025)
MICE has great potential as a driver of inclusive and sustainable economic growth, but the study is still limited. In fact, MICE is not just a tourism subsector, but a node of interaction between industries and regions. This study aims to measure the economic contribution of MICE domestic tourists to the Indonesian economy, both in terms of output, income, employment, and added value, as well as to evaluate sectoral linkages and spillover effects between regions. The methodology used is the Interregional Input-Output (IRIO) model, which tracks economic impacts sectorally and spatially. MICE travelers' spending is converted into a final demand vector, which is then used to calculate changes in output, income, labor, and added value at the provincial and sector levels. The results show that domestic MICE spending generated additional output of IDR 219.10 trillion, revenue of IDR 44.77 trillion, creation of 1.36 million jobs, and added value of IDR 122.75 trillion. The largest sectoral impact was felt in the accommodation, trade, land transportation, and food and beverage sectors. Spatially, provinces such as DKI Jakarta, East Java, and Bali received the greatest absolute benefits, while S.R. Yogyakarta, NTB, and Southeast Sulawesi recorded the highest percentage growth. These findings affirm the role of MICE as a lever for the national economy and a tool for regional equity. In conclusion, the MICE sector has demonstrated its role not only as a driver of economic growth but also as a catalyst for deeper regional economic integration. Recommendations include promoting policies that the impact of MICE is not only temporary, but also the foundation for inclusive and sustainable long-term economic growth.